2012
DOI: 10.1128/aem.07790-11
|View full text |Cite
|
Sign up to set email alerts
|

Toward Homosuccinate Fermentation: Metabolic Engineering of Corynebacterium glutamicum for Anaerobic Production of Succinate from Glucose and Formate

Abstract: ABSTRACTPrevious studies have demonstrated the capability ofCorynebacterium glutamicumfor anaerobic succinate production from glucose under nongrowing conditions. In this work, we have addressed two shortfalls of this process, the formation of significant amounts of by-products and the limitation of the yield by the redox balance. To eliminate acetate formation, a derivative of the type strain ATCC 13032 (str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
133
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(139 citation statements)
references
References 65 publications
(67 reference statements)
3
133
1
2
Order By: Relevance
“…Recent metabolic engineering studies have shown that C. glutamicum is also capable of producing a variety of other commercially interesting compounds, e.g., other L-amino acids (4), D-amino acids (5), organic acids such as succinate (6)(7)(8)(9), diamines such as cadaverine (10,11) or putrescine (12), biofuels such as ethanol or isobutanol (13)(14)(15), and proteins (16)(17)(18).…”
mentioning
confidence: 99%
“…Recent metabolic engineering studies have shown that C. glutamicum is also capable of producing a variety of other commercially interesting compounds, e.g., other L-amino acids (4), D-amino acids (5), organic acids such as succinate (6)(7)(8)(9), diamines such as cadaverine (10,11) or putrescine (12), biofuels such as ethanol or isobutanol (13)(14)(15), and proteins (16)(17)(18).…”
mentioning
confidence: 99%
“…Carboxylic acids such as formate, acetate and propionate can inhibit bacterial cell growth resulting in cellular responses including expression changes (Lee et al, 2006;Litsanov et al, 2012a;Polen et al, 2003). C. glutamicum ATCC 13032 also showed reduced growth rates with increasing formate concentrations (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In enzyme assays with cell-free extracts, we could not detect formate dehydrogenase activity using NAD + or NADP + as cofactors (data not shown). In whole cell biotransformation processes, FDHs are frequently used for cofactor regeneration, like the NAD + -dependent FDH from Mycobacterium vaccae (Bäumchen et al, 2007;Litsanov et al, 2012a). However, FDH from C. glutamicum ATCC 13032 is most likely not applicable for such processes and the oxidation of formate led to the generation of reducing equivalents, which are transferred to a currently unknown electron acceptor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Formate provides a carbon source for nucleic acid biosynthesis. Inflammatory diseases often occur as a result of excessive formate consumption [46]. Even though cows with ketosis are more vulnerable to mastitis and endometriosis [47], it is crucial to understand the relationship between formate and ketosis in dairy cows.…”
Section: Discussionmentioning
confidence: 99%